Behcet Disease: When Laryngeal Tuberculosis Unforeseably Strikes - Chaïmaâ Zeroual (Indonesian Journal of Rheumatology, 2025)
Behçet disease (BD) is a chronic vasculitis that can affect all organs, particularly the skin, mucous membranes, eyes and joints. It can lead to severe complications requiring immunosuppressive therapy (IS). Although the prescription of IS is indisputable and life-saving, they carry a significant risk of opportunistic infections. Tuberculosis is an infectious disease primarily caused by the bacterium Mycobacterium tuberculosis, also known as Koch's bacillus. It predominantly affects the lungs due to airborne transmission and favorable conditions for the bacillus's survival in this area; however, it can also affect other sites to a lesser extent, such as the brain, bones, skin and « ear, nose and throat » (ENT) regions. Laryngeal tuberculosis (LT) is a rare and underdiagnosed localization that often occurs in immunocompromised patients. This article reports the case of a patient with BD under IS who developed LT secondary to subclinical pulmonary tuberculosis. The outcome after discontinuing azathioprine and initiating antituberculous treatment was favorable. The case report aims to shed light on the rare and underrecognized presentation of tuberculosis in BD and in case of immune vulnerability, unraveling the intricate interplay between immunosuppression and opportunistic infections. Its significance lies in underscoring the critical need for heightened clinical vigilance, as LT can masquerade as BD-related manifestations, posing diagnostic dilemmas.